THE TORQUE TEST SPECIMENS ANALYSIS USING FINITE ELEMENT ANALYSIS - Riyadi, Slamet; Setiawan, Tia; Koswara, Engkos (Universitas Majalengka, 2022)
The industrial component of industrial equipment is required to have good quality. The elementsor components of a tool must be light but have strong and corrosion-resistant alloys. Testing ofthe materials to be used must be appropriate and in accordance with the needs. There are severalways, one of which is by using a torque testing machine and Finite Element Analysis (FEA). FiniteElement Method (FEM) or commonly called Finite Element Analysis (FEA), is a numericalprocedure that can be used to solve certain engineering problems. Modeling torsion test objectsusing the FEM with a moment 598.0635 N mm, - 598.0635 N mm with respect to vector Xcounterclockwise. The material used is ASTM A 36 with a mass of 0.0163569 kg and a volume of2083.94 mm^3, torsion test analysis using finite element-based software. Based on thesimulation results, it can be seen that the largest stress (maximum stress) occurs in the XZ vectorwith a value of 10.4783 MPa, while the smallest stress (minimum stress) occurs towards the YZvector with a value of 0.15986 MPa. The largest strain (maximum strain) occurred in vector XZwith a value of 0.000068123 ul, while the smallest strain (minimum strain) occurred in vector XXwith a value of 0.00000107672 ul. The safety factor obtained is 0.71, meaning that the value isless than equal to 1 which indicates that the test object is unable to accept the given load.